Wheat genotypes selected for their high early daytime stomatal conductance under elevated nocturnal temperatures maintain high yield and biomass - Pinto, R. Susuky; Garatuza-Payán, Jaime; Murchie, Erik H.; Reynolds, Matthew Paul; Yépez, Enrico A. (Oxford University Press, 2025)
Global night-time temperatures are increasing and correlate with a decline in crop yield. Various aspects of nocturnal physiology in plants are understudied, one of which is the independent influence on daytime processes. Twelve elite wheat genotypes were field grown in plots with artificially increased night-time temperatures (+ 2 degrees C). The stomatal conductance on the adaxial and abaxial leaf sides were measured during the morning and the night, and stomatal morphological traits were assessed during the same period of plant growth. To determine whether an increase in early daytime stomatal conductance provides a growth and/or yield advantage under high temperature, the biomass (Bm), grain number (Gn), thousand-grain weight (TGW), and grain yield (Yld) were measured. Genotypes exhibiting the highest early daytime stomatal conductance also showed higher Bm, Gn, and Yld. An increase of 19% in early daytime stomatal conductance led to a Yld increase of 86 and 65 gm-2, in heated and control conditions respectively, translating to 43 and 35% Yld enhancement. Irrespective of the environment, the adaxial leaf side showed the highest diurnal and nocturnal conductance, mirroring direct stomatal aperture (SA) measurements. The high night-time temperature treatment increased daytime stomatal conductance but reduced nocturnal conductance. SA varied with growing conditions; in the morning, plants under high night-time temperatures showed larger SA than those from the control independently of the leaf side, conversely, the opposite trend was observed in the night. Stomata on the adaxial leaf side showed higher density and larger size. Results from this study show that early daytime conductance increased productivity in hot-irrigated environments studied here. Previous studies showed that high pre-dawn conductance improves morning photosynthesis, and here we find that high nocturnal temperatures increased early morning conductance but reduced night-time conductance and this may be a factor that contributed to minimize Yld losses.